Mnemonik Sebagai Alternatif dalam Menghafal Kosakata Bahasa Arab - Sari, Risna Rianti (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2018)
In fact, vocabulary cannot be separated from language learning. It was neglected in language teaching programs in order to help the learners understand the language effectively. Nowadays, many researchers have realized that vocabulary is an important part of language learning and teaching. The purpose of the study were to introduce the technique called â€œMnemonicâ€ to Arabic student learners in college. The aim also to explore their creativities during the class by this method in terms of short-term and long-term retention. Students of Arabic learning program, however, reported to frustrate when they face with new words, since they have difficulty retaining them. This  mnemonics devices can be used to solve this problem and to improve their Arabic vocabulary learning, Many kinds of mnemonic can be used to help the learners, there are story method, keyword method, and imagery link. The kinds of mnemonic are undeniably an effective method for accelerating learning of Arabic vocabularies because  it improves immediate recall. Beside aid the memory for memorizing vocabularies, this mnemonic also makes the Arabic learning process enjoy and the other words mnemonic  is a fun method of learning which makes the retrieval process easier by bridging the meaning of words with related the brain hemisphere both right and left brain. Here we will consider the usefull of the method and how to apply it.